Penerapan Media Quizizz pada Mata Pelajaran Matematika untuk Meningkatkan Minat Belajar Siswa Kelas VII SMP Negeri 2 Kadugede - Akbar, Mochammad Ibram; Gustiana, Eva (Indo-MathEdu Intellectuals Journal, 2025)
Mathematics learning in schools is generally still dominated by conventional methods and monotonous material delivery, making it less interesting for students to learn. This study aims to increase students' interest in learning by using the interactive learning media Quizizz. The method used in this research is quantitative with a quasi-experimental design using the research design known as Nonequivalent Control Group Design. The study was conducted at SMP Negeri 2 Kadugede with subjects from class VII B (28 students) as the experimental class and VII C (30 students) as the control class. Data were collected through observation, questionnaires, and interviews. Data analysis techniques using t-test. The results of the analysis show that the average learning interest of students in the experimental class using Quizizz media is 43.75, which is higher than the control class at 32.47, with a difference of 11.28 points. This difference is statistically significant (p = 0.000). The Independent Samples T-Test shows a significance value of 0.000 (< 0.05), which means there is a significant difference in learning interest between the two groups. Thus, H₁ is accepted and H₀ is rejected, indicating that the use of Quizizz media is proven to be effective in increasing students' interest in learning Mathematics at SMP Negeri 2 Kadugede.